Investigation of planar fractal antennas - Temirbayev, A.A.; Imanbayeva, A.K.; Karibayev, B.A.; Namazbayev, T.A.; Kapurnova, S.T.; Tleubayeva, I.S. (Recent Contributions to Physics, 2016)
The paper considers a development and modelling of wide-band fractal antenna intended for use in wireless communication systems and investigation of their electrodynamics characteristics in Ansoft HFSS software package. Planar antennas constructed on the basis of three types of fractals were investigated in this work: anisotropic fractal of Zhanabaev, Sierpinski’s triangle and Sierpinski’s carpet. Received results show that fractal antennas in planar execution proved to be competitive for application in systems of a wireless communication. Modelling results of anisotropic antenna presents that with proper selection of the size and the type of substrate this antenna shows properties of wide-bandness and can be used in wireless Wi-Fi, GPS technology.